HIV-positive mothers’ worries and its implications for nursing care - Sherlock, Maria do Socorro M.; Vieira, Neiva Francenely C. (Brazilian Journal of Sexually Transmitted Diseases, 1999)
ln the last decade, the public health system worldwide has been greatly challenged in attempts to con-trol the rapid spread of the Human Immune Defici-ency Vírus (HIV) that causes the Acquired Immune Deficiency Syndrome (Aids). The number of children with aids who got the vírus from their mothers has increased dramatically. Nowadays there are around 1000 infected children with HIV in the world. This study explores the feelings and expectations from mothers with HIV/ Aids while waiting their children medical exams for HIV infection. It intends to show the implications caused by this tension on mother self-care. This investigation adopted a descriptive approach and embraced principies from the qualitative method. Data was collected through interviews conducted with mothers who are assisted in the public health service. The findings showed that mothers tend to reduce t heir self-care in arder to provide better attention to their children. ln doing so, likely they run the risk to d evelop Aid s more rapidly. Thus, this study suggests that the nursingassistance for mothers with HIV/ Aids must reinforce the need of self-care, including their children as part of the care.